ERO1-β, a pancreas-specific disulfide oxidase, promotes insulin biogenesis and glucose homeostasis - Ester Zito; King‐Tung Chin; Jaime D. Blais; Heather P. Harding; David Ron (2010)
Mammals have two genes encoding homologues of the endoplasmic reticulum (ER) disulfide oxidase ERO1 (ER oxidoreductin 1). ERO1-β is greatly enriched in the endocrine pancreas. We report in this study that homozygosity for a disrupting allele of Ero1lb selectively compromises oxidative folding of proinsulin and promotes glucose intolerance in mutant mice. Surprisingly, concomitant disruption of Ero1l, encoding the other ERO1 isoform, ERO1-α, does not exacerbate the ERO1-β deficiency phenotype. Although immunoglobulin-producing cells normally express both isoforms of ERO1, disulfide bond formation and immunoglobulin secretion proceed at nearly normal pace in the double mutant. Moreover, although the more reducing environment of their ER protects cultured ERO1-β knockdown Min6 cells from the toxicity of a misfolding-prone mutant Ins2Akita, the diabetic phenotype and islet destruction promoted by Ins2Akita are enhanced in ERO1-β compound mutant mice. These findings point to an unexpectedly selective function for ERO1-β in oxidative protein folding in insulin-producing cells that is required for glucose homeostasis in vivo.